(untitled) (Czech Journal of Multidisciplinary Innovations, 2022)
The article examines the views of representatives of various scientific schools on the problems of taxation. The evolution of scientific views determining the role of the state in taxation issues is shown. The tendency of convergence of scientific theories, scientific and methodological approaches to the implementation of tax policy is noted.